Trust based knowledge acquisition for conversation agents - Goh, Ong Sing; Fung, C.C. (International Association of Engineers, 2008)
This paper explores the study of conversation agent knowledge bases particularly, its relationship to the related study of information trustworthiness and knowledge acquisition. Some important methods for knowledge extraction from online documents are discussed in this paper. This is done in relation to the purpose of the design and development of domain-specific information for CAs? knowledge bases. This paper focuses on a novel approach based on the proposed Web Knowledge Trust Model (WKTM) and the Automated Knowledge Extraction Agent (AKEA). The results indicate that WKTM is useful for evaluating the trustworthiness of web sites and it is useful for the developing of key criteria for a knowledge acquisition for conversation agents.